2015
DOI: 10.3906/tar-1407-29
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genetic diversity among Chinese watermelon germplasmsusing SSR and SRAP markers, and implications for future genetic improvement

Abstract: The genetic diversity of watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] in China, the world's largest producer of watermelon fruits, has not been examined. Two molecular markers, sequence-related amplified polymorphism (SRAP) and simple sequence repeat (SSR), were used to investigate the genetic variation and genetic relationship among 54 Chinese watermelon accessions, as well as 7 accessions from Africa, the United States, and Japan. SRAP assay generated 312 bands, of which 163 were polymorphic, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
3
5
1
Order By: Relevance
“…In addition, the Turkish watermelons were slightly different from four popular cultivars (36, Sugar Baby; 39, Crimson Sweet; 233, Calhoun Gray; and 235, Charleston Gray) (Figure 1). Geography-based clustering among the Turkish watermelons did not exist in this study, which was also consistent with previous reports of watermelons (Solmaz et al, 2010;Ocal et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the Turkish watermelons were slightly different from four popular cultivars (36, Sugar Baby; 39, Crimson Sweet; 233, Calhoun Gray; and 235, Charleston Gray) (Figure 1). Geography-based clustering among the Turkish watermelons did not exist in this study, which was also consistent with previous reports of watermelons (Solmaz et al, 2010;Ocal et al, 2014;Wang et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…For example, data produced with SRAP, inter-simple sequence repeat (ISSR), random amplified polymorphic DNA (RAPD), and peroxidase gene-based polymorphism markers had a correlation value of 0.81 as verified by the Mantel test, but data of RAPD markers always had lower correlation values (about 0.7). Hence, SRAP-based estimation of relationships highly correlates with the results of most marker systems such as simple sequence repeat, amplified fragment length polymorphism, and ISSR (Wang et al, 2015). For estimating genome sampling size, one approach is to use a set that covers the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al (2012) detected a total of 94 putative alleles, similar to the current study. However, this was lower than 133, 101 and 795 alleles detected by Zhang et al (2016), Wang et al (2015) and Reddy et al (2015) among watermelon accessions, respectively. Nimmakayala et al (2009) reported a total of 169 alleles amplified in watermelon accessions.…”
Section: Discussioncontrasting
confidence: 66%
“…In a comparative study of genetic diversity between C. lanatus germplasms using SSR and SRAP markers, Wang et al. () found that the most germplasms were grouped separately based on their geographical distribution and horticultural classification and have low genetic variations.…”
Section: Discussionmentioning
confidence: 99%